Pelatihan Berpikir Kritis untuk Mereduksi Bandwagon Syndrome pada Remaja - Siti Fatimah; Tiara Agustine; Feni Solihah; Ahmad Syafi’i; Riani Suminar (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2025)
The bandwagon syndrome phenomenon is getting stronger among teenagers in the digital era, where the tendency to follow the majority trend without rational consideration hinders the development of independent thinking. This intervention aims to measure the effectiveness of critical thinking training in reducing bandwagon syndrome in 95 MA Miftahurroja students. The quasi-experimental method with a pre-test post-test design is used with a bandwagon syndrome understanding questionnaire instrument, a critical thinking skills questionnaire, and a behavior observation sheet. Intervention is carried out through three stages: interactive education, decision-making simulation, and continuous assistance with the Digital Critical Thinking Learning Platform (DCTLP). The results showed a significant increase in the understanding of bandwagon syndrome from 28% to 82% (t=19.234, p<0.001) and critical thinking skills from 35% to 76% (t=17.456, p<0.001). Behavioral observation shows that 60% of students experience a change in a more critical and independent mindset. The aspect of a critical attitude towards information develops the highest (77.5%), while confidence in acting differently requires reinforcement (57.5%). Research proves that the integration of digital technology in critical thinking training is effective in reducing bandwagon syndrome and can be replicated in other educational institutions.